Effects of advanced carbohydrate counting on glucose control and quality of life in children with type 1 diabetes. Issue 7 (3rd August 2020) - Donzeau, Aurelie; Bonnemaison, Elisabeth; Vautier, Vanessa; Menut, Vanessa; Houdon, Laure; Bendelac, Nathalie; Bismuth, Elise; Bouhours‐Nouet, Natacha; Quemener, Emmanuel; Baron, Sabine; Nicolino, Marc; Faure, Nathalie; et al.
Abstract: Objective: The effect of advanced carbohydrate counting (ACC) on metabolic and quality of life (QOL) outcomes is uncertain in children with type 1 diabetes. Our aim was to determine whether ACC would improve HbA1c and QOL scores as compared with standard nutrition in this population. Methods: We randomized 87 patients using pump and rapid‐acting analogs in a 1 year randomized multicenter study (age 9.6 ± 3.5 years, diabetes duration 4.6 ± 2.7 years, HbA1c 7.8 ± 0.5% [62 ± 5 mmol/mol]). The ACC group received CC education and the control group received traditional dietary education. HbA1c was measured every 3 months. At 0 and 1 year, general, diabetes‐specific, and diet‐related QOL were respectively assessed by the KIDSCREEN and WHO‐5 questionnaires, the diabetes‐specific module of the DISABKIDS, and the diet restriction items of the DSQOLS. Results: Mean HbA1c was lower in the ACC than the control group at 3 months ( P < .05) and tended to be lower at 6 months ( P = .10), 9 months ( P = .10), but not at 12 months. The mean of individual average HbA1c during the one‐year study period (from M3 to M12) was 7.63 ± 0.43 in the ACC vs 7.85 ± 0.47% in the control group (60 ± 5 vs 62 ± 5 mmol/mol)( P < .05). ACC was associated with significantly higher scores at 1 year on the KIDSCREEN children's psychological scale and the KIDSCREEN parents' physical scale, the DISABKIDS children's treatment scale, and the children's and parents' dietary restriction scales of the DSQOLS (indicating better QOL or lower perceived diet restriction). Conclusions: ACC may be associated with small improvements in metabolic control and QOL scores in children.